Identifikasi Senyawa Aktif dalam Daun Dadap Serep (Erythrina subumbrans (Hassk.) Merr) dan Potensinya sebagai Antioksidan - Nauval, Lailatul Azizah Okta; Wijayatri , Ratna; Oktaviyani , Tiwi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Erythrina subumbrans (Hassk.) Merr, locally known as dadap serep, is a medicinal plant traditionally used to treat various ailments, suggesting the presence of bioactive compounds. Scientific exploration of its phytochemical profile and antioxidant potential, however, remains limited compared to other species in the genus. Objective: This study aimed to (1) identify the bioactive compound groups in the 70% ethanol extract of Erythrina subumbrans leaves through phytochemical screening and Thin Layer Chromatography (TLC), and (2) evaluate its antioxidant activity quantitatively using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging method. Methods: The leaves were extracted via maceration using 70% ethanol. The extract was subjected to standard phytochemical screening tests for flavonoids, alkaloids, saponins, and tannins. Flavonoid profiling was performed using TLC with a quercetin standard. Antioxidant activity was assessed by the DPPH method, with vitamin C as a reference standard, and the IC₅₀ value was determined. Results: Phytochemical screening confirmed the presence of flavonoids, alkaloids, saponins, and tannins. TLC analysis indicated the presence of flavonoid compounds, with one major spot showing an Rf value similar to the quercetin standard. The DPPH assay revealed that the extract possesses strong antioxidant activity, with an IC₅₀ value of 49.94 ppm. According to established antioxidant strength criteria, this IC₅₀ value is categorized as very strong.Conclusion: The 70% ethanol extract of Erythrina subumbrans leaves contains diverse bioactive compounds, particularly flavonoids, and exhibits very strong antioxidant activity. These findings scientifically support its traditional use and highlight its potential as a promising source of natural antioxidants for further pharmaceutical or nutraceutical development.